(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper focuses on the improvement of Expectation Maximization algorithm. A method attribute selection for experimentation on Expectation Maximization (EM) clustering is used. In attribute selection we used Gain Ration Attribute Eval, Ranker method for EM clustering, which gives better results than the result obtain without using attribute selection method.